Tendencias de la Educación Ambiental en el Contexto de la Educación Básica y Media de Colombia en los Últimos Diez Años. 2010 – 2020. (2021)
This research has as its main goal to evaluate teaching and learning practices in environmental education for basic and middle school in Colombia, between 2010 and 2020. Check it, in the intention of studying and analyzing the main conceptual themes and methodologies currently applied in terms of environmental education inside the classroom. The study was performed using a qualitative and descriptive method, based on the use of logic, analysis, and following an inductive process to understand theoretical notions obtained from a bibliographic compilation made from several authors. As part of the process, classification matrixes were built and analyzed repeat identify distinct categories that were useful to delve into different aspects of the subject in the context of basic and middle school in Colombia in the last 10 years. A significant remark in the six categories developed in the research is made about the importance of environmental education as one of the principal tools in society’s transformation, as well as the promotion of values, conscience, and the raising of awareness among kids and young-adults who are the future actors that will produce all the changes needed in the world.